2022
DOI: 10.3389/fpsyg.2022.813206
|View full text |Cite
|
Sign up to set email alerts
|

Does Technical Match Performance in Professional Soccer Depend on the Positional Role or the Individuality of the Player?

Abstract: The aim of the study was to examine the impact of the positional role and the individuality on the technical match performance in professional soccer players. From official match data of the Bundesliga season 2018/19, technical performance [short (<10 m)/medium (10–30 m)/long (>30 m) passes, dribblings, ball possessions] of all players who played during the season were analyzed (normative data). Five playing positions (center back, full back, central midfielder, wide midfielder and forward) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Their distribution among positions and match outcomes are summarized in Tables 3-6. Five different playing positions were categorized (central defender, full back, central midfielder, wide midfielder, forward) (Chmura et al, 2021;Forcher et al, 2022a;Modric et al, 2022). For the first team, the definitions were made in consultation with an assistant coach directly involved in the line-up and substitutions.…”
Section: Study Design and Research Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Their distribution among positions and match outcomes are summarized in Tables 3-6. Five different playing positions were categorized (central defender, full back, central midfielder, wide midfielder, forward) (Chmura et al, 2021;Forcher et al, 2022a;Modric et al, 2022). For the first team, the definitions were made in consultation with an assistant coach directly involved in the line-up and substitutions.…”
Section: Study Design and Research Methodsmentioning
confidence: 99%
“…To some extent, this observation may be explained by the fact that the individual match observations in the U18 compared to the U21 originate to a greater extent from offensive positions. Offensive positions are associated with higher external match loads, especially distancerelated measures (Altmann et al, 2021;Forcher et al, 2022a;Rico-Gonzalez, Oliveira, Palucci;Vieria, Pino-Ortega, & Clemente, 2022). In their systematic review Palucci Vieira et al (2019) reported increasing match running loads with aging in youth players when determined with fixed speed thresholds.…”
Section: Age-related Match Loadsmentioning
confidence: 99%
See 3 more Smart Citations